Analysis of The Relationship Between Attitude and Leadership in Improving The Performance of Harvest Foremen: A Case Study of Oil Palm Plantations - Wandha Atmaka Aji (Akademi Komunitas Perkebunan Yogyakarta, 2026)
This study analyzes the relationship between attitude and leadership in improving the performance of harvest supervisors in oil palm plantations. Harvest supervisors play a strategic role as a link between management and field workers, where their personal attitude and leadership quality directly affect productivity and the quality of fresh fruit bunches (FFB). A quantitative descriptive approach was employed through case studies in several estates in South Sumatra, involving 118 respondents. The attitude variable was measured through indicators such as integrity, commitment, loyalty, innovation, and self-confidence, while the leadership variable included work instructions, task distribution, work evaluation, motivation, and occupational health and safety (OHS). Results show that the average score for attitude was 3.26 and for leadership 3.29 (on a 1–4 scale). Performance distribution indicated 15% of supervisors in category A (76), 65% in category B (56–75), and 20% in category C (55). A positive correlation was found between positive work attitudes and effective leadership, which contributed to higher performance outcomes. Estate E achieved the highest scores (3.93), while Estate C recorded the lowest (3.00–3.06). These findings highlight the need to strengthen innovation, motivation, and OHS practices as priorities in supervisor development programs. The study contributes to human resource management in agribusiness by providing practical recommendations, particularly leadership training based on positive work attitudes, to sustainably improve harvest performance.